S30 CEACAM5 (CD66e) mucosal immunoreactivity and its relationship to asthma. (December 2018) - Tanner, AR; Ward, J; Wilson, S; Howarth, P
Abstract : Introduction: The CEACAM immunoglobulin superfamily receptors are involved in cell signalling, cell proliferation and cell repair responses and have relevance to the maintenance of the intact bronchial epithelium. A number of these family members recognise bacteria and, as such, are part of the host defence response. However, some CEACAM-binding bacterial pathogens, in particular Haemophillus influenzae, exploit the binding capacity to enhance their chances of colonizing the mucosal surface. As there is increased Haemophillus presence within the airways in severe asthma, linked to neutrophilic airway inflammation, we investigated the presence of CEACAM5 within endobronchial biopsies by immunohistochemistry in health and in asthma. CEACAM5 was selected is one of the main bacterial binding immunoglobulins of relevance. Method: Immunohistochemical staining for submucosal CEACAM5 expression was performed on GMA embedded endobronchial biopsies from healthy controls (n=16), mild asthmatics (n=12) and severe asthmatics (n=15). Epithelial immunoexpression (percentage epithelial area using KS400 software) and sub-mucosal positive cell count quantification was undertaken. Sequentially cut sections, stained with neutrophil elastase and CEACAM5, were analysed by the Camera Lucida system to identify the percentage of submucosal positive CEACAM5 cells that were neutrophils. Results: Epithelial immunoreactivity was significantly greater in severe asthma than in health (p=0.027). There was insufficient intact and orientated epithelium to derive quantitative measures in the mild asthmatics. Median CEACAM5 immunoreactive sub-mucosal cell count/mm 2 was significantly higher in severe asthma (37.1 cells), than in both health (15.5, p≤0.001) and mild asthma (23.6, p=0.037). There was no significant difference between health and mild asthma. The median percentage CEACAM5-neutrophil positive submucosal cells in severe asthmatics (n=5) was 52%, with the range being 50%–90.63%. Conclusion: CEACAM5 expression is higher in the epithelium and submucosa of severe asthmatics. This has potential relevance to the altered airway microbiome and biofilm formation in severe asthma. As such, CEACAM5 targeted therapies could be of benefit. Longitudinal studies to understand this relationship would be desirable.